2019
DOI: 10.1039/c9fo00254e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Momordica saponin extract on alleviating fat accumulation in Caenorhabditis elegans

Abstract: The study offers methods and models for elucidating fat accumulation and mechanisms, valuable for studies of other plant-based nutraceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…The PPAR may have different target genes dependent to co-factors, such as C/EBPs and PPAR coactivator 1α (PGC1α) ( Chung et al., 2016 ); PGC1α and C/EBPβ were both involved in the increased fatty acid oxidation by CPT1 in human nasopharyngeal cancer cells ( Du et al., 2019 ). Homologs of these co-factors are MDT-15/PGC1α and CEBP-2/C/EBP in C. elegans , respectively ( Lin et al., 2019 , Xu et al., 2015 ). However, neither MDT-15 nor CEBP-2 was identified as co-factors for the isorhamnetin's fat-lowering effects via NHR-49-mediated pathway in the current study, which also explain the null effect of isorhamnetin on cpt-5 /CPT1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PPAR may have different target genes dependent to co-factors, such as C/EBPs and PPAR coactivator 1α (PGC1α) ( Chung et al., 2016 ); PGC1α and C/EBPβ were both involved in the increased fatty acid oxidation by CPT1 in human nasopharyngeal cancer cells ( Du et al., 2019 ). Homologs of these co-factors are MDT-15/PGC1α and CEBP-2/C/EBP in C. elegans , respectively ( Lin et al., 2019 , Xu et al., 2015 ). However, neither MDT-15 nor CEBP-2 was identified as co-factors for the isorhamnetin's fat-lowering effects via NHR-49-mediated pathway in the current study, which also explain the null effect of isorhamnetin on cpt-5 /CPT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-obesity mechanisms of action of dietary bioactives and plant extracts on lipid metabolism have various molecular targets in C. elegans ( Farias-Pereira et al., 2018 , Lin et al., 2019 , Liu et al., 2018 , Machado et al., 2018 , Shen et al., 2017 , Shen et al., 2018c , Sun et al., 2016 , Yue et al., 2019 ). It was reported that the inhibitory effects of NHR-49 on fatty acid desaturases (lipogenesis) were related to the fat-lowering effects of a saponin extract in C. elegans ( Lin et al., 2019 ). AAK was found to be regulated for isorhamnetin and methylated resveratrol associated with fatty acid oxidation and lipogenesis, respectively ( Yue et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the saponin content, none of the triterpenoid saponins identified in CV have yet been investigated. However, an isolated triterpenoid saponin from Panax ginseng [ 95 ], a steroidal saponin from Asparagus racemosus [ 96 ], and plant extracts particularly rich in triterpenoid saponins [ 97 , 98 ] were previously reported to enhance stress resistance and to prolong lifespan in C. elegans . In the study of Magid et al [ 50 ], saponins accounted for only 0.5% of the total composition of a methanol extract of piquiá shells.…”
Section: Resultsmentioning
confidence: 99%
“…11 Interestingly, we also noted the potential of CPPs and MSs in relieving fat deposition and improving resistance in C. elegans. [13][14][15][16] Therefore, MSs may be a dietary supplement to treat obesity and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%